English Pronunciation Errors Made By English Department Students Of Muhammadiyah University Of Sumatera Barat - Anjelina, Fizi; Syam, Erlinda (Inovasi Pendidikan, 2023)
This research has several purposes. The first wa to find out and analyze type of errors english pronunciation made by students. The next purpose was to find out the reasons for pronunciation errors. The research was conducted at English Department Students Of Muhammadiyah University Of Sumatera Barat, which involved 15 students including 4th, 6th and 8th semester. This study collected data through tests and interviews, generating qualitative information. The data was analyzed using percentages and frequencies to obtain data results. The results showed that the English department students of muhammadiyah of west sumatera made 149 errors. the types of pronunciation errors were divided into 3 types, namely, substitution, omission and insertion. pronunciation errors were divided into two indicators, namely consonant sounds and vowel sounds. Consonant has the highest frequency of substitution 56 (92%), followed by omission 4 (6%) and the lowest is insertion 1 (2%). Then in vowel sounds, the highest frequency of errors ws omission 50 (57%), followed by substitution 38 (43%) and the lowest was insertion 0 (0%). On the other hand, the reason for making the highest error was interference as many as 6 students, followed by fosizilation as many as 2 students, CA as many as 2 students and finally Markedness differential as many as 2 students.Keyword : analysis errors, pronunciation